Bound States in the Continuum versus Fano Resonances: Topological Argument - Denis V. Novitsky; Andrey V. Novitsky (Photonics, 2022)
There is a recent surge of interest to the bound states in the continuum (BICs) due to their ability to provide high-quality resonances in open photonic systems. They are usually observed in perturbed systems possessing Fano resonances in their spectra. We argue that, generally speaking, the Fano resonances should not be considered as a proxy for BICs (as it is often done) due to their fundamentally different topological properties. This difference is illustrated with the non-Hermitian layered structure supporting both topologically nontrivial quasi-BIC and topologically trivial Fano resonances. Non-Hermiticity can also be a source of additional topological features of these resonant responses. Moreover, the lasing mode associated with BIC in this structure also possesses nonzero topological charge that can be useful for producing unconventional states of light. This paper contributes to the discussion of BIC physics and raises new questions concerning topological properties of non-Hermitian systems.